2004
DOI: 10.1093/ajcn/80.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Moderate wine drinkers have lower hypertension-related mortality: a prospective cohort study in French men

Abstract: A moderate intake of wine is associated with a lower risk of mortality from all causes in persons with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 21 publications
2
24
1
2
Order By: Relevance
“…No comparisons were made with normotensive individuals. Total mortality has been investigated in prior studies [9,[12][13][14]24], but with inconsistent conclusions about the potential beneficial effects of a light-to-moderate alcohol intake in men with hypertension [9,14]. We found that moderate drinkers had a lower all-cause mortality than non-drinkers and heavy drinkers, which seems to apply to both men and women with normal blood pressure and hypertension.…”
Section: Discussionmentioning
confidence: 65%
“…No comparisons were made with normotensive individuals. Total mortality has been investigated in prior studies [9,[12][13][14]24], but with inconsistent conclusions about the potential beneficial effects of a light-to-moderate alcohol intake in men with hypertension [9,14]. We found that moderate drinkers had a lower all-cause mortality than non-drinkers and heavy drinkers, which seems to apply to both men and women with normal blood pressure and hypertension.…”
Section: Discussionmentioning
confidence: 65%
“…Recent large epidemiological studies on cardiovascular health include those by Grønbaek et al [55] (13,064 men and 11,459 women; follow-up about 10 years), Renaud et al [56] (36,583 men; follow-up 13-21 years), and Klatsky et al [57] (56,926 men and 72,008 women; followup 20 years or known death). From these studies, a conservative estimate on the reduced risk of cardiovascular mortality for moderate drinkers of red wine (1-3 glasses a day) amounts to 0.7 compared to nondrinkers.…”
Section: Studies On Winementioning
confidence: 99%
“…Previous studies on resveratrol and wine polyphenols were indicative of their role in the prevention of cardiovascular diseases, since a number of epidemiological findings À known as "French Paradox" À have revealed an inverse correlation between the red wine consumption and cardiovascular disease incidences (Renaud & de Lorgeril, 1992;Renaud et al, 2004). In addition, trans-resveratrol exhibits significant anticancer (Jang et al, 1997), antiinflammatory, antibacterial, (Chan, 2002) and phytoestrogenic properties (Gehm, McAndrews, Chien, & Jameson, 1997).…”
Section: Introductionmentioning
confidence: 99%